2018
DOI: 10.1016/j.jcbs.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Early sudden gains in an acceptance and values-based intervention: Effects on treatment outcome for depression and psychological flexibility

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In fact, accumulating evidence suggests that psychological inflexibility is associated with higher levels of depressive symptoms in individuals with chronic pain [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Additionally, ACT for chronic pain alleviates depressive symptoms by improving psychological inflexibility [ 22 , 25 , 26 , 27 , 28 , 29 , 30 ]. One study [ 31 ] found that psychological inflexibility predicted severe depressive symptoms in 144 patients with chronic pain, independent of the effect of their pain intensity, mindfulness, and pain-related acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, accumulating evidence suggests that psychological inflexibility is associated with higher levels of depressive symptoms in individuals with chronic pain [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Additionally, ACT for chronic pain alleviates depressive symptoms by improving psychological inflexibility [ 22 , 25 , 26 , 27 , 28 , 29 , 30 ]. One study [ 31 ] found that psychological inflexibility predicted severe depressive symptoms in 144 patients with chronic pain, independent of the effect of their pain intensity, mindfulness, and pain-related acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…The delayed effect of participant 1 reached significance after two weeks. A study by Keinonen et al ( 2018 ) found that 25% of patients can experience a sudden gain (an abrupt reduction in symptom severity after which they stabilize) after the first two sessions of an ACT intervention. It seems likely, also looking at his graph, that participant 1 experienced a sudden gain in depression scores after session two.…”
Section: Discussionmentioning
confidence: 99%
“…Value affirmation interventions have been shown to help improve grades and to help support the sense of personal worth and integrity [ 31 ]. Past clinical trials that used value-based interventions reported reduced severity of depression symptoms in patients [ 39 ]. Additionally, results from our recently published study on Kenyan adolescents, in which this value-based approach—a component of the Shamiri intervention—was used, suggest that promoting value reflection may reduce mental health problems and improve psychosocial outcomes in adolescents in sub-Saharan Africa [ 20 , 34 ].…”
Section: Interventionsmentioning
confidence: 99%